Global development finance : (The World Bank, 2007)
Global Development Finance is the World Bank’s annual review of global financial conditions facing development countries. Current volume provides analysis of keys trends and prospects, including coverage of capital raised by developing country based corporations. The Volume I consists of main chapters: One: The Outlook for Development Countries; Two: Financial Flows to Development Countries: Recent Trends and Prospects; Three: The Globalization of Corporate Finance in Development Countries